Islamic Jurisprudential differences in (Expiations and Oaths) in the book "Almoghni" of Imam Ibn Qudaamah - Jurisprudential comparative study - Alsawadi, Omama smeer (Journal of Islamic Sciences, 2022)
The study aimed to collect and confine the three jurisprudential differences stated by Ibn Qudaamah in his book Almoghni, in the section of Expiations, and the chapter of Oaths. In addition to illustrating the similarities and his methodology in dealing with jurisprudential differences. The study also was based on an inductive and deductive approach. The study axes included the difference between the expiation of swearing by God and Zakat al-Fitr in terms of giving the debt priority over them if they run out of money. Besides, the difference between the inability to perform vowed fasting and the inability to perform obligatory fasting in terms of the obligation of expiation. In addition, the difference between one who made a vow to walk to a mosque to pray in it and one who made a vow to worship on a specific day in terms of the obligation to perform the vow. Findings showed that the most common and oldest definition of the science of jurisprudences differences is “the art that mentions the difference between the united counterparts in their imagery and meaning, and different in judgment and reason at the same time”. Moreover, the science of jurisprudence is of great benefit, as it leads the Muslim to the appropriate judgment; then preserves the security and stability of the Muslim community. As well, the distinctiveness of Ibn Qudama with his sharp intelligence, because all the differences in the section of Expiations and the chapter of Oaths were three strong differences.
Keywords: Jurisprudential Differences; Expiations; Oaths; Almoghni; IbnQudaamah; The Hanbalis